Salivary and serum concentrations of monocyte chemoattractant protein‐1, macrophage inhibitory factor, and fractalkine in relation to rheumatoid arthritis and periodontitis - Yilmaz Dogukan; Gönüllü Emel; Gürsoy Mervi; Könönen Eija; Gürsoy Ulvi Kahraman (American Academy of Periodontology, 2022)
Background: Monocyte chemoattractant protein-1 (MCP-1), macrophage migration inhibitory factor (MIF), and fractalkine are chemokines that are expressed by a variety of cell types to regulate macrophage inflammatory response. The aim of the study was to examine the effects of periodontitis and rheumatoid arthritis (RA) on their serum and salivary concentrations.
Methods: Adults with either periodontitis (P, n = 21), or with rheumatoid arthritis (RA, n = 23), or with both diseases (RA+P, n = 23) were included in the study. Systemically and periodontally healthy individuals (n = 22) served as controls. Saliva and serum samples were collected from all participants before the medical and periodontal examinations. Salivary and serum MCP-1, MIF, and fractalkine concentrations were measured by the Luminex technique. Total salivary protein levels were determined by the Bradford assay.
Results: Salivary MCP-1, MIF, and fractalkine concentrations were elevated in both RA groups (RA+P and RA) in comparison with systemically healthy controls. As related to total salivary protein levels, higher MCP-1 (P = 0.003) and fractalkine (P = 0.045) concentrations were found in controls compared with the P group. In serum, MCP-1 concentrations in the RA+P group were higher (P = 0.003) than those of group P. Elevated serum fractalkine concentrations were observed in both periodontitis groups (RA+P, P = 0.014; and P, P = 0.013) compared with controls.
Conclusions: In RA, MCP-1, MIF, and fractalkine concentrations are elevated in saliva. These chemokines may disrupt oral macrophage responses and potentially take part in the interaction between periodontitis and RA.